ANALISIS PELAKSANAAN PROGRAM GERDU TASKIN TERHADAP PENINGKATAN VOLUME USAHA RUMAH TANGGA MISKIN BERPOTENSI (RTM-B) DI DESA BEDAHLAWAK KECAMATAN TEMBELANG KABUPATEN JOMBANG - ASMA'UL HUSNA (Jurnal Pendidikan Akuntansi (JPAK), 2013)
This research was conducted to determine the extent of the impact of the program on the volume of business Gerdu Taskin poor households potentially (RTM-B) in the Village District Bedahlawak Tembelang Jombang. The research was quantitative descriptive research and conducted in the village Bedahlawak order to analyze the impact of this program on the target group and the business volume RTM-B. The results showed Program Gerdu Taskin a concrete impact on the increase in business volume RTM-B by providing operating funds. And the results of the analysis of the volume of business with the RTM-B Program Gerdu Taskin in the Village District Bedahlawak Tembelang Jombang the business volume increased by 65%, while that has not been increased or equal to 27.5% the previous state, and which decreased only 7,5%. Based on the results of this study suggested. Taskin Gerdu program in the village in the future not only focus on providing venture capital, but also small business coaching or training. Keywords: Anaysis,Gerdu Taskin Program, Business Volume